Team Learning in Finnish Engineering Curricula: A Data Mining Approach - Koivunen, Sakari; Mikkilä-Erdmann, Mirjamaija; Iiskala, Tuike (Belgium, 2026)
Teamwork is a critical skill in engineering practice, yet previous studies suggest that recently graduated engineers often lack sufficient collaboration and communication skills. Despite its importance, team learning is rarely addressed from a curriculumlevel perspective in academic literature, and data mining methods are seldom used to analyze engineering curricula. This study investigates how team learning is represented in the declared curricula of 18 Finnish Universities of Applied Sciences offering full-time Bachelor of Engineering programs starting in Fall 2024. A dataset of 9509 course descriptions was collected using a custom-built web crawler. After initial filtering with regular expressions, 2178 course descriptions were manually analyzed and categorized according to five criteria related to team learning, such as prerequisites, learning outcomes, assessment methods, learning activities, and project work. The results reveal that team skills are explicitly listed as a learning outcome in 677 courses and as part of assessment in 369 courses. However, only six courses mention team skills as a prerequisite. Team learning methods are often vaguely described, and project work is frequently mentioned without clarification on whether it is team-based. We argue that team learning should be treated as a curriculum-level competence that is intentionally developed throughout engineering studies. This study contributes a large-scale, data-driven perspective and lays the groundwork for further in-depth qualitative analysis.
53rd Annual Conference of the European Society for Engineering Education. 2025 Proceedings : Engineering and Society